Adaptations to chronic rapamycin in mice. Issue 1 (1st January 2016) - Dodds, Sherry G.; Livi, Carolina B.; Parihar, Manish; Hsu, Hang-Kai; Benavides, Adriana D.; Morris, Jay; Javors, Martin; Strong, Randy; Christy, Barbara; Hasty, Paul; Sharp, Zelton Dave
Abstract : Rapamycin inhibits mechanistic (or mammalian) target of rapamycin (mTOR) that promotes protein production in cells by facilitating ribosome biogenesis (RiBi) and eIF4E-mediated 5'cap mRNA translation. Chronic treatment with encapsulated rapamycin (eRapa) extended health and life span for wild-type and cancer-prone mice. Yet, the long-term consequences of chronic eRapa treatment are not known at the organ level. Here, we report our observations of chronic eRapa treatment on mTORC1 signaling and RiBi in mouse colon and visceral adipose. As expected, chronic eRapa treatment decreased detection of phosphorylated mTORC1/S6K substrate, ribosomal protein (rpS6) in colon and fat. However, in colon, contrary to expectations, there was an upregulation of 18S rRNA and some ribosomal protein genes (RPGs) suggesting increased RiBi. Among RPGs, eRapa increases rpl22l1 mRNA but not its paralog rpl22 . Furthermore, there was an increase in the cap-binding protein, eIF4E relative to its repressor 4E-BP1 suggesting increased translation. By comparison, in fat, there was a decrease in the level of 18S rRNA (opposite to colon), while overall mRNAs encoding ribosomal protein genes appeared to increase, including rpl22, but not rpl22l1 (opposite to colon). In fat, there was a decrease in eIF4E relative to actin (opposite to colon) but also an increase in the eIF4E/4E-BP1 ratio likely due to reductions in 4E-BP1 at our lower eRapa dose (similar to colon). Thus, in contrast to predictions of decreased protein production seen in cell-based studies, we provide evidence that colon from chronically treated mice exhibited an adaptive 'pseudo-anabolic' state, which is only partially present in fat, which might relate to differing tissue levels of rapamycin, cell-type-specific responses, and/or strain differences.